THE ORIGINS OF FINANCIAL PROVISIONS IN THE SOUTH AFRICAN SCHOOLS ACT - Bembe, Nomfundo Patience (My University, 2011)
This research investigated the emergence on of financial provisions in the South Africa Schools Act (SASA). This was motivated by the need to understand key issues that helped to shape education policies in postapartheid South Africa and specifically to analyse the bottlenecks and factors that affected the policy transformation phase. The purpose of this research is to understand key issues that helped to shape education policies in post-apartheid South Africa and to examine factors that affected the policy transformation process. The research used qualitative methodology in order to collect in-depth information from various respondents. The research employed both qualitative interviews and document analysis as a way of data collection techniques. The research shows that the circumstances during the formulation of SASA do not support the notion that neo-liberal ideologies have direct implications for policy development in South Africa. It was recommended that further research could be undertaken on how these policies could best be improved to achieve desirable outcomes
MM thesis - P&DM
Keywords: Schools Act, South Africa; Finance, Schools